WONG LAYANG: PROBLEMS OF WELFARE OF FISH PROCESSORS IN BAJOMULYO VILLAGE - Syifa Annisa Nurnajmi; Nabiel Muhammad Mashabi; Adyatma Adzanta Bilhaq; Farhan Nurdin; Fadhlan Irsyad; Rai Sanggara (Cinematology: Journal Anthology of Film and Television Studies, 2022)
As we know, several factors that weigh a person's well-being in any field of work are very important and needed. For example, things that can affect the poverty and welfare of coastal communities, because the low income of fishermen is still a factor causing the lack of welfare of the fishing community in their work. The lack of openness of insight and an active and creative mindset in improving a resource is still not enforced, so this results in a lack of environmental economic value and income. This study describes the condition of the community in Bajomulyo village, Juwana district. The method used in this study is a qualitative method with a descriptive analysis approach. Data obtained from the process of observation, interviews, documentation and literature studies. This study found that there was a competition in the fishing business between those who used a broker and those who did not use a broker. So because of this, there is an income gap between those who use brokers and those who don't. The implications of this research can be a reference for the fisheries and marine service in determining and providing policies on the process of buying and selling flying fish, especially in Bajomulyo village, Juwana district. All of this research data is the main data in making documentary films.